Efficacy of dietary supplements on sports performance outcomes: a systematic review of evidence in elite athletes - Yu, Tongwu; Ding, Chuanwei (Frontiers in Nutrition, 2025)
ObjectiveTo systematically evaluate the efficacy of dietary supplements for enhancing athletic performance specifically in elite athletes, considering supplement type, dosing protocols, and sport-specific demands.MethodsThis PRISMA-adherent systematic review (INPLASY202411036) searched PubMed, Web of Science, Scopus, and SportDiscus (Jan 2014-Nov 2024) for randomized controlled trials (RCTs) or controlled clinical trials examining dietary supplement interventions in elite athletes, compared to placebo/no intervention, reporting quantitative performance outcomes. Methodological quality was assessed using the PEDro scale; risk of bias was evaluated with the Cochrane Risk of Bias Tool V.2. Narrative synthesis was performed due to outcome heterogeneity.ResultsForty-six studies (n = 928 participants) met inclusion criteria, with predominantly male participants (60%). Performance enhancers showed varying efficacy: caffeine (3–6 mg/kg) consistently improved power output and technical performance; beta-alanine demonstrated sport-specific benefits; while nitrate supplementation showed limited effects in elite populations. Recovery supplements displayed mixed results, with amino acids and probiotics showing promise for fatigue prevention and exercise tolerance. Studies demonstrated high methodological quality (average PEDro score: 10.65/11), though female athletes were underrepresented (10% of studies).ConclusionDietary supplement efficacy in elite athletes is highly variable, contingent upon supplement type, sport-specific demands, individualized dosing protocols, and athlete characteristics (including potential gender differences). Caffeine and certain amino acid/probiotic formulations demonstrate the most consistent benefits. Findings strongly support individualized, evidence-based supplementation strategies over generic protocols. Future research must address the significant gender gap and underrepresentation of specific sports.